ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMK PADA MATERI MATRIKS - Mochamad Zaviar Firdaus Suherlan; Martin Bernard; Luvy Sylviana Zanthy (IKIP Siliwangi, 2023)
This research has a purpose or intent to analyze the mathematical problem solving abilities of SMK students in the matrix subject by using indicators consisting of 4 main components, including: (1) understanding the problem; (2) planning problems; (3) solve the problem of the appropriate plan; also (4) reviewing or re-checking the steps taken. And the data analysis method used in this research is using qualitative and descriptive methods. The subjects in this study were 10 students of SMK Mitradharma Cililin class X. The instrument of this research was 4 questions about the matrix. The results found in this study is that it can be seen that the level of students' mathematical problem solving abilities is low. Therefore, further research is needed on student problem solving to produce additional data that can be used as assessment and analysis material to create learning models that can improve learning outcomes, especially those related to students' mathematical problem solving abilities.